Identifikasi Penyebab Penyakit Bercak Merah pada Tanaman Stroberi (Fragaria sp.) di Bali dan Potensi Pengendaliannya dengan Jamur Antagonis Secara In Vitro - SANTIKADEWI, I GUSTI AYU ARI; WIRYA, GUSTI NGURAH ALIT SUSANTA; PHABIOLA, TRISNA AGUNG; SUPUTRA, I PUTU WIRYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.2, April 2022, 2022)
Identification of Pathogenic Fungi causes Red Leaf Spot on Strawberry Plants ( Fragaria sp.) in Bali and Control Potential with Antagonist Fungi Strawberry ( Fragaria sp.) is a subtropical fruit plant that was first discovered in Chile, America and has high economic value. Strawberry plants growing in Bali show symptoms of pathogenic fungi attack. Symptoms include red spots on the leaf surface. The purpose of this study was to identify pathogenic fungi that cause disease in strawberry plants in the center of strawberry cultivation in Bali. The activities carried out in this study were (1) sampling, (2) isolation of pathogenic fungi from symptomatic strawberry plant parts, (3) pathogenicity test, (4) morphological identification of pathogenic fungi, and (5) potential inhibition test of antagonistic fungi. against pathogenic fungi. This research was conducted in Pancasari Village, Buleleng Regency and Candi Kuning and Kembang Mertha Villages, Tabanan Regency and continued at the Plant Disease Laboratory, Faculty of Agriculture, Udayana University, Denpasar. The results of this study succeeded in identifying Pestalotiopsis sp. as a pathogen causingred spot disease on strawberry leaves in Bali and the potential for biological control using antagonistic fungi in vitro showed that Gliocladium sp. and Trichoderma asperellum can suppress the growth of pathogenic fungi on strawberry plants by > 80%, Trichoderma viride up to > 90% and Trichoderma koningii and Trichoderma harzianum up to > 50%.